Comparison of the Kinetic Properties of Crude and Purified Xylanase from Bacillus pumilus with Commercial Xylanase from Aspergillus niger - Kapilan, R.; Arasaratnam, V. (My University, 2011)
Xylanases showing better stability at alkaline pH and higher temperatures have potential applications in several industrial processes. The objective of this study is to compare the kinetic properties and stability of crude and purified xylanase from Bacillus pumilus with commercial xylanase from Aspergillus niger. Bacillus pumilus which can grow and produce xylanase above 40oC and pH 9.0 was selected for this study. Crude, purified and commercial xylanases showed zero order kinetics for 10 minutes and highest activity was obtained at 60°C and pH 9.0. The optimum pH for crude, purified and commercial xylanases were 9.0, 9.0 and 7.0 respectively at 60°C and the Michaelis constant by Lineweaver-Burk Plot for xylan were 3.1, 2.3 and 0.03gL-1 under the respective optimized conditions. The half-life of the crude and purified xylanase was highest at pH 9.0 and 50°C while that for the commercial enzyme was at pH 7.0 and at 60°C.
Keywords: Xylanase; Kinetic properties; Michaelis constant; Vmax; Stability; Half life